The Influence of Financial Performance on Firm Value with Dividend Policy as a Moderating Variable - Nuryaman Nuryaman; Nur Hasanah (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
This study aims to use dividend policy as a moderator to analyse the relationship between financial performance and business value. Utilising a quantitative methodology, this research takes a descriptive and verificative approach. All coal businesses trading on the IDX between 2019 and 2022 make up the study population. This study employed a purposive sampling strategy with predetermined criteria to choose 12 businesses for analysis, yielding 48 observations. The data used in this study is secondary data obtained from the official website of the Indonesia Stock Exchange at www.idx.co.id. Methods for gathering information include documenting and reviewing existing publications. Using Eviews 9 software, data is processed and analysed using methods such as panel data regression analysis, multiplecollinearity and heteroscedasticity tests, t-tests and F-tests for hypothesis testing, and study of the coefficient of determination. This study found that: (1) firm value is affected by liquidity; (2) firm value is not affected by leverage; (3) firm value is affected by profitability; (4) dividend policy cannot moderate the relationship between liquidity and firm value; (5) dividend policy can moderate the relationship between leverage and firm value; and (6) dividend policy cannot moderate the relationship between profitability and firm value.